Effect of implant design on the initial biomechanical stability of two self-tapping dental implants. (April 2020) - Hsieh, Min-Chieh; Huang, Chang-Hung; Lin, Chun-Li; Hsu, Ming-Lun
Abstract: Background: This study evaluated the effect of two self-tapping implants on implant stability in immediate implantation. Methods: Two types of self-tapping implants, straight flute (STF) and spiral flute (SPF) designs, were studied. Two synthetic bone blocks with varying densities (0.32 g/cm 3 and 0.16 g/cm 3 ) were chosen to simulate the bone quality of the anterior maxilla. Insertion torque values were measured by a torque testing machine during implant insertion. Four biomechanical tests were performed: resonance frequency analysis was conducted using the Osstell device, and the strengths of screw push-in, lateral bending, and pull-out were evaluated using an MTS machine. The strength for each design feature was obtained by averaging the results of 10 trials. In total, 40 specimens were tested for each bone density. Statistical difference was determined by one-way analysis of variance followed by Bonferroni post hoc multiple tests between groups. Findings: The STF and SPF groups exhibited similar insertion torque values ( p = 0.525 in low-density bone, and p = 0.99 in high-density bone). A significant difference ( p < 0.001) was observed in the push-in test between the two groups when low-density bone was tested. The SPF group exhibited a significantly higher lateral bending force ( p = 0.001) and a higher stiffness ( p < 0.001) than the STF group in high-density bone. The SPF design attained higher ( p < 0.001) ISQ numbers than the STF design, but all numbers were below 60. Interpretation: Implant stability can be influenced by the apical fixture design of self-tapping implants in immediate implantation. Highlights: Clinical success of immediate implantation depends on favorable initial bone- screw stability. The effect of the cutting flute design in self-tapping screws was analyzed. Spiral and straight cutting flute designs exhibit different strengths under loadings. Clinicians should choose an appropriate implant design according to clinical situation.